Communicating the Greatest Story on Earth - S. H. Wittwer (Journal of Applied Communications, 1972)
One hundred years ago it was not easy to sell science to society and "book learning" to farmers and legislators, but gradually the image developed that research was valuable to farmers, and they, in turn, influenced legislators and congressmen to support research.